2011
DOI: 10.17578/15-3/4-2
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Bank Long-term Lending Behavior:Evidence from Russia

Abstract: We investigate the determinants of the banks' propensity to make long-term business loans in an emerging market context. Using a large sample of Russian banks, we find that the median bank allocates only 0.5% of its assets in long-term business loans and that there is wide cross-sectional variation in this ratio among banks. A bank's ability to extend long-term business loans depends on its size, capitalization, and the availability of long-term liabilities rather than its type of ownership. These results high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 27 publications
(19 reference statements)
6
26
0
1
Order By: Relevance
“…7, No. 5;2015 Furthermore, the results indicated that the financial health and liquidity in banks play a vital role in determining the credit, and the good economic conditions induce banks to increase the volume of credit provided to the private sector. Sharma and Gounder (2012) examined the change in the bank credit provided to the private sector in six economies in the South Pacific during the period 1982-2009.…”
Section: Bank Credit In Jordanmentioning
confidence: 99%
See 4 more Smart Citations
“…7, No. 5;2015 Furthermore, the results indicated that the financial health and liquidity in banks play a vital role in determining the credit, and the good economic conditions induce banks to increase the volume of credit provided to the private sector. Sharma and Gounder (2012) examined the change in the bank credit provided to the private sector in six economies in the South Pacific during the period 1982-2009.…”
Section: Bank Credit In Jordanmentioning
confidence: 99%
“…7, No. 5;2015 where BC/TA , represents the proportion of the credit facilities to the total assets provided from the bank i in the period t. DEP/TA , represents the ratio of deposits to the total assets of the bank i in the period t. NPLs , is the ratio of the non-performing loans to the total loans of the bank i in the period t. CAP , is the ratio of the capital to the total assets of the bank i in the period t. LIQ , represents the liquidity ratio to the total assets of the bank i in the period t. SIZE , is the natural logarithm of the size of the assets of the bank i in the period t. WR is the interest rate on the funds deposited in the window of deposit for the Central Bank of Jordan in the period t. LR is the average interest rate on the loans in period t. DR is the average interest rate on the deposits in period t. RR is the legal reserve ratio imposed by the Central Bank of Jordan on the banks in period t. INF is the inflation rate in Jordan during the period t. GRTH is the rate of growth in the GDP in the period t.…”
Section: The Study Modelmentioning
confidence: 99%
See 3 more Smart Citations